KUALITAS KIMIA DAN SENSORIS KARAMEL SUSU KAMBING DENGAN PENAMBAHAN BUAH NANAS (Ananas comosus L. Merr.) - , RACHMAD BAMBANG S ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This experiment was conducted to investigate the effect of pineapple (Ananas comosus) addition on chemical and sensory quality of goat milk caramel, âve to find out the best level of pineapple addition. The materials in this research was goat's milk and additives. The addition level of pineapple were 0, 10, 20, and 30% of milk volume. The data of chemical quality i.e. water, protein, fat contain, and total carbohydrate were analyzed by analysis of variance of 2x4 factorial (two before and after ripening and additioning four level of pineapples) of Completely Randomized Design. Replication for each treatment was 3 times. The means of diferences were tested by Duncanâs New Multiple Ranges Test (DMRT). Sensory quality data was tested with non-parametric statistical analysis with hedonic test of Kruskal Wallis. The results showed that the addition of pineapple there was significant different (P<0,01) on the levels of water contain and sensory qualities. The addition of pineapple there was significant (P<0,05) on the levels of protein, fat, and total carbohydrate. The addition of pineapple incerased water contain of caramel milk ranged from 7,98 o 14,83, total carbohydrate of caramel milk ranged from 5,01 to 8,76, and also sensory qualities. Protein contain increased in milk caramel with 10% of pineapple addition, in concentration fat contain was descreased. In conclution, the best level of pineapple addition is 10%.